A study on the need to implement the no-fault liability scheme for motor vehicle accident claims in Malaysia /Ahmad Faris Khairudin...[et al.] - Khairudin, Ahmad Faris; Zakaria, Nor Zahidah; Hamdan, Nurul Rafeeza; Mohamad, Rayhan (2010)
This research aims at determining the necessity to implement the No-Fault Liability Scheme replacing the current Fault-Based System for motor vehicle accidents in Malaysia. The reason why the topic was chosen is because motor vehicle accident is a matter that concerns every Malaysian citizens as it inevitably affects one's life and perception on the consequence of motor vehicle accidents. There are still many Malaysians who are not aware of their motor vehicle insurance and its function. Nevertheless, the current law regulating motor vehicle accidents is not meeting the objective of restoring all injured parties' livelihood as justice delayed is justice denied, A team of four members conducted this research as part of a compulsory requirement prior to the completion of Bachelor in Legal Studies (Hons) degree in Universiti Teknologi MARA Malaysia. There are five chapters in this research that discusses and analyzes the inadequacies in the current Fault-Based System and the need to implement the No-Fault Liability Scheme. The No-Fault Liability Scheme is centered on upholding distributive justice and maximizes public's welfare through prompt compensation and quick return to society. The chapters begin with an introduction on motor vehicle accidents in Malaysia and its regulation and the proposed implementation of the No-Fault Liability Scheme. The next chapter is on literature review, followed by a chapter on commentaries on current local motor vehicle accidents cases, subsequently a chapter on findings from the interviews held with four key stakeholders in the motor vehicle industry. Lastly, the conclusive chapter entails recommendations to implement the NFL Scheme in Malaysia.